2016
DOI: 10.1016/j.polymer.2016.02.029
|View full text |Cite
|
Sign up to set email alerts
|

A comparative parameter study: Controlling fiber diameter and diameter distribution in centrifugal spinning of photocurable monomers

Abstract: In this study, key factors for controlling the average fiber diameter and diameter distribution of fibers made via simultaneous centrifugal spinning and UV initiated polymerization are elucidated. Through systematic investigation, it was found that average fiber diameter has a strong dependence on monomer delivery rate through the orifice, which can be intuitively linked to both the orifice diameter and monomer mixture viscosity. On the other hand, the breadth of the fiber diameter distribution can be controll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(54 citation statements)
references
References 53 publications
2
50
0
2
Order By: Relevance
“…According to the previous experiments, it was found that when the spinning temperature was below 200 °C, the melt viscosity was too high for the spinning condition, causing unstable flow and hence the large droplet When the spinning temperature was above 240 °C, oxidation and thermal degradation starts to occur as indicated by the yellowness of the fibers, and its strength was weak . So, we chose 200–240 °C as the spinning temperature.…”
Section: Methodsmentioning
confidence: 99%
“…According to the previous experiments, it was found that when the spinning temperature was below 200 °C, the melt viscosity was too high for the spinning condition, causing unstable flow and hence the large droplet When the spinning temperature was above 240 °C, oxidation and thermal degradation starts to occur as indicated by the yellowness of the fibers, and its strength was weak . So, we chose 200–240 °C as the spinning temperature.…”
Section: Methodsmentioning
confidence: 99%
“…13 The viscosity of spinning solution is the other important parameter. 12 It also affects the nanofiber fabrication in the process of centrifugal spinning. The viscous force prevents the jet shape changing rapidly and helps to form smooth nanofibers.…”
Section: The Surface Tension and Viscosity Of Spinning Solutionmentioning
confidence: 99%
“…In order to realize the ordered nanofiber collection, many scholars have made a lot of attempts and gained some experience, which provided useful reference for the subsequent studies. 12,50,60 Badrossamay and Senthilram studied the effect of the relationship between the collection distance and the solvent evaporation time on collecting ordered fibers when the concentration of solution and the motor speed were constant. For different polymer solution jets, the characteristic parameters are quite different.…”
Section: The Study On Orderly Nanofiber Collection and Nanospinning Mmentioning
confidence: 99%
See 1 more Smart Citation
“…The size scale of the nanofibers, similar to that of cellular components, can mimic that of the extracellular matrix of biological tissues, and interactions at the molecular level could be exploited to enhance the therapeutic potential of functional agents loaded within nanofibers 4 , 16 , 17 . Different techniques including vapor deposition 18 , 19 , phase separation 11 , 20 , 21 , self-assembly 22 24 and centrifugal spinning 25 27 can be used to synthesize such nanofibers, but electrospinning is the most widely adopted one due to its advantages for implementation/commercialization purposes 28 31 .…”
Section: Introductionmentioning
confidence: 99%